A primer of reliability theory - Grosh, Doris Llyod (New York: John Wiley & Sons, 1989)
A first course in reliability theory. Introduces all the fundamentals and includes derivations. Covers life testing, nonseries-parallel systems, choice of model (for plotting positions), and incorporates the use of electronic spreadsheets.
Introduction -- Reliability distributions -- Multicomponent systems -- Standby redundancy -- Life testing -- The sequential probability ratio test -- Availability and Maintainability -- Military standards
Includes bibliography and index
Keywords: Reliability Theory